Phylogenetic niche conservatism and plant diversification in South American subtropical grasslands along multiple climatic dimensions - Barros,Michel J.F. (2020)
Abstract Phylogenetic niche conservatism can be investigated at multiple scales on an explicit geographical context. Haplotype-based comparative analyses of lineages occupying the same region, and thus subjected to similar environmental factors, allow decoupling shared evolutionary and ecological patterns, as well as multiple dimensions of adaptive diversification. Here we aimed to assess the role of environmental drivers on diversification of subtropical grassland, based on haplotypic diversity of two plant genera. We sampled two closely related and co-distributed grassland plant genera, Petunia and Calibrachoa, across their entire distribution area. Eigenvectors extracted from pairwise distances based on chloroplast DNA haplotypes were used to fit Phylogenetic Signal-Representation (PSR) curves to estimate evolutionary patterns in 19 bioclimatic variables and altitude. The PSR curves showed that altitude, precipitation, and temperature variables changed at different rates with haplotype differentiation. Altitude and temperature traits evolved under conditions closer to a neutral dynamics, whereas precipitation traits differentiated following more complex models. Our results indicated that the diversification in the two genera was more limited by precipitation conditions. Based on these novel findings, we suggest that future studies should test the possible impact of precipitation variables on the process of ecological differentiation in these genera.